Pembuatan Aplikasi Pemberi Informasi Pemberhentian Kereta Api Secara Otomatis Berbasis Android - Ade Pratama Putra Santoso; Kristo Radion Purba (Jurnal Infra, 2017)
Automated Mobile Traffic Automobile Dispatching Applications Supported by Transportation Info And Public Facilities Indonesia is a country that is famous for its many places and uses private transportation of each region, which is used by both economic and executive class people. The train is now very easy to use because people can buy tickets online or directly to the nearest station. Trains are now very easy to get in as many of the trains are in effect.This application is made with java and json programming languages, and uses GPS technology, notifications and googlemaps.Database uses mysql and data taken from E-BOOK railway in 2015.From this application that is on a bad internet connection affect the performance, such as sending data to the server or retrieve data from the server so that it slows the load of data and images. Testing the exact distance and notification to the destination succeeded. Applications can add to the list of Alerts, Notifications and nearby stations. The results of the questionnaire that has been done is the percentage of user ratings of the overall 80% said the application is very good, 20% said the application is good.